PROSPEK NARAPIDANA SETELAH MENJALANI PEMBEBASAN BERSYARAT DAN HAMBATANNYA DALAM PELAKSANAAN PEMBEBASAN BERSYARAT - Siti Saropah (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT The granting of parole to prisoners is the last link of the convict's fostering business in the penal system. By means of parole, inmates can improve communication with the wider community, rediscover their self-worth as human beings and their existence as members of society. In this conditional exercise it must be considered or based on correctional principles, one of which states that during the loss of freedom of movement, prisoners should be introduced to society and should not be alienated from it. By observing one of these principles, it is hoped that the implementation of parole as a means to foster prisoners based on the penal system in achieving its aims and objectives. Factors that are an obstacle or barrier to the implementation of parole are as follows: The inmate concerned still has other cases that have not yet been decided by the court; The prisoner concerned has not received remission or legal deduction; Prisoners who are recidivists; The convicted prisoner during the fostering of the Penal Institution violates; Inmates who underwent less than one year of crime; The Correctional Officer does want conditional exemption to be increased, but the prisoner often commits an offense while in the Penitentiary, so that his administrative requirements do not support prisoners being sent for parole. Sometimes the decline of the parole decree is delayed and if something like this happens then the inmates themselves will be confused, while the officers have tried as much as possible, the prisoners may feel that the prison officers made it difficult to issue the decree. From these communities, parole often encounters obstacles that make prisoners feel less acceptable, for example the families of the victims are still grudging against the prisoners concerned and there is a perception from the public that these prisoners after leaving and getting parole may disturb the order and security of the neighborhood his place. Keywords: Parole